Clinical Significance of Variants in the TTN Gene in a Large Cohort of Patients With Sporadic Dilated Cardiomyopathy - Xiao, Lei; Li, Chenze; Sun, Yang; Chen, Yanghui; Wei, Haoran; Hu, Dong; Yu, Ting; Li, Xianqing; Jin, Li; Shi, Leming; Marian, Ali J.; Wang, Dao Wen (Frontiers in Cardiovascular Medicine, 2021)
Background: Mutations in the TTN gene are the most common causes of dilated cardiomyopathy (DCM). Clinical significance of TTN gene variants remains inadequately understood. Methods: Whole exome sequencing and phenotypic characterization were performed and patients were followed up for a median of 44 months. Results: We analyzed association of the TTN variants with the clinical outcomes in a prospective study of 1,041 patients with sporadic DCM patients. TTN truncating variants (tTTN) were detected in 120 (11.5%) patients as compared to 2.4/10,000 East Asian populations in the GnomAD (p < 0.0001). Pathogenic TTN missense variants were also enriched in DCM as compared to the GnomAD populations (27.6% vs. 5.9%, p < 0.0001). DCM patients with tTTN had a lower left ventricular ejection fraction (28.89 ± 8.72 vs. 31.81 ± 9.97, p = 0.002) and a lower frequency of left bundle branch block (3.3% vs. 11.3%, p = 0.011) as compared to those without or with mutations in other known causal genes. However, tTTN were not associated with the composite primary endpoint of cardiac death and heart transplantation during the follow up period (adjusted HR: 0.912; 95% confidence interval: 0.464 – 1.793; p = 0.790). There was also no sex-dependent effect. Concomitant tTTN and pathogenic variants in other known causal genes were present in only 8 DCM patients and did not affect the outcome. Conclusion: The phenotype of DCM caused by tTTN, major causes of sporadic DCM, are not distinctly different from those caused by other causal genes for DCM. Keywords: DCM, TTN, genetics, phenotype, prognosis